Lead markets in age-based innovations - Nils Levsen; Cornelius Herstatt (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2014)
The trend of population aging is affecting an increasing number of countries around the world, especially advanced economies. One consequence of a growing population share of aged persons is a shift in consumer needs, reflected by a rising number of products and services designed particularly for elderly users. Thus, population aging is a catalyst for new markets and a driver of innovation. A common objective of such age-based innovations is the delay of an age-associated decline in individual autonomy or the restoration of autonomy losses already incurred. In particular, age-based innovations aim to compensate ageassociated deficiencies in sensory perception, cognitive skills, and musculoskeletal status. Age-based innovations are marked by a high level of heterogeneity, both in terms of functionality (e.g. mobility, mental stimulation, financial services) and in terms of industry (e.g. consumer electronics, automotive, banking). Different countries undergo population aging at different times and with different magnitude. As some countries have experienced the phenomenon earlier than others, they have had more time to react and create innovations in response to it. This brings about the question of lead markets - country markets with the characteristic that product or process innovation designs adopted early become the globally dominant design and supersede other innovation designs initially adopted or preferred by other countries (Beise 2001, p.10). Do such lead markets exist within the field of age-based innovations? Moreover, is there possibly a single lead market which consistently leads adoption and diffusion across the heterogeneous range of age-based innovations? Finally, is extant lead market theory applicable to the entirety of age-based innovations - a field of business, where innovation is driven not only by profitability-focused stakeholders but also by a multitude of other stakeholders? These questions delineate a research gap at the intersection of lead market research and age-based innovations research. In order to answer them, a multi-methodology approach was adopted. [...]
Keywords: 330